Adequacy of samples obtained via percutaneous core-needle rebiopsy for EGFR T790M molecular analysis in patients with non-small cell lung cancer following acquired resistance to first-line therapy: A systematic review and meta-analysis. (2021) - Poudel, Bibhav; Desman, Jacob; Aihara, Gohta; Weidman, Deborah I.; Tsang, Ashley; Kovrizhkin, Katherine; Pereira, Tatiana; Arun, Siddharth; Pradeep, Tejus; Matin, Shababa; Liddell, Robert P.
Highlights: While bronchoscopic biopsy methods result in fewer biopsy-related complications, percutaneous core-needle biopsy (PT-CNB) is superior in its ability to obtain more tissue. Rebiopsies characterizing resistance mutations in patients with non-small cell lung cancer (NSCLC) can guide personalized medicine and improve overall survival rates. Percutaneous core-needle lung biopsies obtain adequate samples for molecular characterization of the acquired resistance mutation T790M in patients with NSCLC. Abstract: Micro Abstract: Rebiopsies characterizing resistance mutations in patients with non-small cell lung cancer (NSCLC) can guide personalized medicine and improve overall survival rates. In this systematic review, we examine the suitability of percutaneous core-needle biopsy (PT-CNB) to obtain adequate samples for molecular characterization of the acquired resistance mutation T790M. This review provides evidence that PT-CNB can obtain samples with high adequacy, with a mutation detection rate that is in accordance with prior literature. Background: Non-small cell lung cancer (NSCLC) comprises 85% of all lung cancers and has seen improved survival rates with the rise of personalized medicine. Resistance mutations to first-line therapies, such as T790M, however, render first-line therapies ineffective. Rebiopsies characterizing resistance mutations inform therapeutic decisions, which result in prolonged survival. Given the high efficacy of percutaneous core-needle biopsy (PT-CNB), we conducted the first systematic review to analyze the ability of PT-CNB to obtain samples of high adequacy in order to characterize the acquired resistance mutation T790M in patients with NSCLC. Methods: We performed a comprehensive literature search across PubMed, Embase, and CENTRAL. Search terms related to "NSCLC, " "rebiopsy, " and "PT-CNB" were used to obtain results. We included all prospective and retrospective studies that satisfied our inclusion and exclusion criteria. A random effects model was utilized to pool adequacy and detection rates of the chosen articles. We performed a systematic review, meta-analysis, and meta-regression to investigate the adequacy and T790M detection rates of samples obtained via PT-CNB. Results: Out of the 173 studies initially identified, 5 studies met the inclusion and exclusion criteria and were chosen for our final cohort of 436 patients for meta-analysis. The pooled adequacy rate of samples obtained via PT-CNB was 86.92% (95% CI: [79.31%, 92.0%]) and the pooled T790M detection rate was 46.0% (95% CI: [26.6%, 66.7%]). There was considerable heterogeneity among studies (I 2 > 50%) in both adequacy and T790M detection rates. Conclusion: PT-CNB can obtain adequate samples for T790M molecular characterization in NSCLC lung cancer patients. Additional prospective studies are needed to corroborate the results in this review.